IMPROVING STUDENTS’ SPEAKING SKILLS USING VIDEO - Fitriyeni, Fitriyeni; Widyastuti, Tri (Aksara Public, 2020)
Online learning has become one of the teaching and learning method to be implemented in this pandemic Covid-19. To make students gain their curiosity in understanding topics being learned, teachers should give interesting and real materials for them, and video is one of the necessary audio visual that can represent the real situation of the topics because through video, the teacher can give factual information and explanation, and the students will feel connected with their teacher. This research studied the use of videos in teaching speaking through the e-learning system. The method used is quasi-experimental research that the researchers applied for two groups, experimental and control group. The sample of this research is 100 students of English 1 in the even semester of 2019-2020. The result shows that there is a significant impact of the use of the video in teaching speaking. It gives the greater result for improving students' speaking skills than not using the video. The positive contribution of using videos in teaching speaking gives positive impact in improving the students' understanding of the topics being learned, as it is known that the students tend to enjoy watching audio visual materials rather than reading or visual materials. as video is really important to enhance the students interests and motivation towards learning to communicate, for they will have the real examples of the situations being discussed.